Illusztrált hagyomány: A Piroska és a farkas új (képi) interpretációi - Margittai , Zsuzsa (Studia Litteraria, 2019)
To each well-known fairy tale belongs a tradition of visual adaptations formed in centuries and still being formed and transformed. The alteration of visual interpretations also effects the story itself. The paper gives examples of this transformation from Hungarian children’s book illustration of today, amongst them the so-called Design book series and a picture book designed especially for blind people, which reinterprets the idea of a picturebook. Parallel to international trends these tendencies also refer to the transmedia storytelling conception of Henry Jenkins, while they strengthen the reception of the story through multisensorial perception.